A companion to translation studies (Multilingual Matters Ltd., 2007)
This book provides a guide to key approaches in translation studies.The book is divided into 9 specialist areas: culture, philosophy, linguistics, history, literary, gender, theatre and opera, screen, and politics. Each chapter gives an in-depth account of theoretical concepts, issues and debates which define a field within translation studies.